(untitled) (Third Sector Social Economic Review, 2024)
The aim of this study is to examine and evaluate the effects of professional accountants’ perceptions of dissatisfaction with technological products on their retirement planning processes in line with the rapidly increasing use of digital and technological products in today’s workplaces. One of the important factors affecting transformation in the business world is digital and technological developments. Undoubtedly one of the most important professional groups affected by such developments is accountants. In the study, it was examined what kind of effects professional accountants’ perceptions of digital and technological innovations, which have gained great momentum recently and frequently used in practice, might have within the scope of their retirement planning processes, and empirical methods were used thanks to the use of appropriate scales. Various statistical inferences were provided by data analysis. As a result of the study, it was determined that the dissatisfaction perceptions of professional accountants who use digital and technological products in their workplaces had a significant effect on their retirement planning processes (β: 0.125 p<0.05). It is thought that the study will provide important gains to decision makers at the management level and especially professional accountants about their retirement planning processes in the future.